Fixed Point Results in Fuzzy Strong Controlled Metric Spaces with an Application to the Domain Words - Aftab Hussain; Umar Ishtiaq; Hamed Al Sulami (Advances in Mathematical Physics)
In this manuscript, we introduce the notions of fuzzy strong controlled metric spaces, fuzzy strong controlled quasi-metric spaces, and non-Archimedean fuzzy strong controlled quasi-metric spaces and generalize the famous Banach contraction principle. We prove several fixed point results in the context of non-Archimedean fuzzy strong controlled quasi-metric space. Furthermore, we use our main result to obtain the existence of a solution for a recurrence problem linked with the study of Quicksort algorithms.